Subarachnoid Block as a Sole Anesthesia for Emergency Surgical Procedures in Two High-risk Former Preterm Infants - Gupta, Anju; Gupta, Nishkarsh (Journal of Neonatal Surgery, 2019)
Several reports have described spinal anesthesia as a preffered technique of anaesthesia for preterm infants undergoing inguinal herniorrhaphy. However, it is not used routinely probably due to lack of awareness and fear of adverse events. We are reporting the successful use of spinal anaesthesia for two high risk preterm infants posted for emergency procedures.